The ethical implications of HCI’s turn to the cultural - Benford, Steve; Greenhalgh, Chris; Anderson, Bob; Jacobs, Rachel; Golembewski, Michael; Jirotka, Marina; Stahl, Bernd Carsten; Timmermans, Job; Giannachi, Gabriella; Adams, Matt; Row Farr, Ju; Tandavanitj, Nick; et al. (Association for Computing Machinery, 2015)
We explore the ethical implications of HCI’s turn to the ‘cultural’. This is motivated by an awareness of how cultural applications, in our case interactive performances, raise ethical issues that may challenge established research ethics processes. We review research ethics, HCI’s engagement with ethics and the ethics of theatrical performance. Following an approach grounded in Responsible Research Innovation, we present the findings from a workshop in which artists, curators, commissioners, and researchers explored ethical challenges revealed by four case studies. We identify six ethical challenges for HCI’s engagement with cultural applications: transgression, boundaries, consent, withdrawal, data, and integrity. We discuss two broader implications of these: managing tensions between multiple overlapping ethical frames; and the importance of managing ethical challenges during and after an experience as well as beforehand. Finally, we discuss how our findings extend previous discussions of Value Sensitive Design in HCI.